Genetic Diversity Study on Geographical Populations of the Multipurpose Species Elsholtzia stauntonii Using Transferable Microsatellite Markers - Zhang, Chenxing; Jia, Chunfeng; Liu, Xinru; Zhao, Hanqing; Hou, Lu; Li, Meng; Cui, Binbin; Li, Yingyue (Frontiers in Plant Science, 2022)
Elsholtzia stauntonii Benth. (Lamiaceae) is an economically important ornamental, medicinal and aromatic plant species. To meet the increasing market demand for E. stauntonii, it is necessary to assess genetic diversity within the species to accelerate the process of genetic improvement. Analysis of the transferability of simple sequence repeat (SSR) markers from related species or genera is a fast and economical method to evaluate diversity, and can ensure the availability of molecular markers in crops with limited genomic resources. In this study, the cross-genera transferability of 497 SSR markers selected from other members of the Lamiaceae (Salvia L., Perilla L., Mentha L., Hyptis Jacq., Leonurus L., Pogostemon Desf., Rosmarinus L., and Scutella L.) to E. stauntonii was 9.05% (45 primers). Among the 45 transferable markers, 10 markers revealed relatively high polymorphism in E. stauntonii. The genetic variation among 825 individuals from 18 natural populations of E. stauntonii in Hebei Province of China was analyzed using the 10 polymorphic SSR markers. On the basis of the SSR data, the average number of alleles (NA), expected heterozygosity (HE), and Shannon’s information index (I) of the 10 primers pairs were 7.000, 0.478, and 0.688, respectively. Lower gene flow (Nm = 1.252) and high genetic differentiation (Fst = 0.181) were detected in the populations. Analysis of molecular variance (AMOVA) revealed that most of the variation (81.47%) was within the populations. Integrating the results of STRUCTURE, UPGMA (Unweighted Pair Group Method with Arithmetic Mean) clustering, and principal coordinate analysis, the 825 samples were grouped into two clusters associated with geographical provenance (southwestern and northeastern regions), which was consistent with the results of a Mantel test (r = 0.56, p < 0.001). Overall, SSR markers developed in related genera were effective to study the genetic structure and genetic diversity in geographical populations of E. stauntonii. The results provide a theoretical basis for conservation of genetic resources, genetic improvement, and construction of a core collection for E. stauntonii.